Ultrastructural changes in peripheral arteries and nerves in diabetic ischemic lower limbs, by electron microscope - Mohamed E. Salem; Abdel-Azzem A. Ismael; Amr Salem; Tarek Salem (Alexandria Journal of Medicine, 2017)
Background: The results of “light and electron microscopic study” of the peripheral arteries and nerves biopsies in diabetic neuropathy comparing with biopsies of normal arteries and nerves of traumatic amputation as a control group. Aim of the work: To evaluate the “electron microscopic changes” in the peripheral small arteries and nerves in the diabetic ischemic lower limbs. Patients and methods: From January 2015 to June 2016 a total number of 20 patients with diabetic ischemic lower limbs (Diabetic patients group) compared with 20 non diabetic non ischemic persons as (Control group) who undergone traumatic lower limb amputation. All cases were subjected to complete history taking, complete clinical examination, and routine laboratory investigations. “Light and electron microscopic studies” of biopsies from the peripheral small arteries and nerves e.g. digital or posterior tibial arteries and nerves during amputation of diabetic gangrene of the toes, below knee, above knee amputation and from traumatic amputation of the control group. Results: The results of an “electron microscopic study” of diabetic peripheral arteries and nerves biopsies, 12 out of 20 cases showed thrombi in small vessels. In some small vessels, masses of fibrin were seen within the lumen. In other vessels, older thrombi were present. 17 out of 20 cases showed endothelial cells hyperplasia in some vessels. The degree of hyperplasia was sufficient to occlude the lumen of the vessels. Some vessels showed degenerate pericytes and endothelial cells which contained large lipid droplets. The peripheral nerves showed patchy demyelination, areas of degeneration and regeneration, areas of infarction and necrosis and collagen fibers deposition. Among the control group, no cases contained thrombi, degenerated vessels, degenerate pericytes or lipid droplets within the endothelial cells. Conclusion: The present study found that the diabetic microangiopathy is the main cause of diabetic neuropathy and diabetic foot lesions.